Calcined Clays for Sustainable Concrete Proceedings of the 2nd International Conference on Calcined Clays for Sustainable Concrete - Martirena, Fernando; Favier, Aurélie; Scrivener, Karen; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2018)
This volume focuses on research and practical issues linked to Calcined Clays for Sustainable Concrete. The main topics are geology of clays, hydration and performance of blended system with calcined clays, alkali activated binders, applications in concrete and mortar, durability of concrete under various aggressive conditions, and economic and environmental impacts of the use of calcined clays in cement based materials. This book compiles the different contributions of the 2nd International Conference on Calcined Clays for Sustainable Concrete, which took place in La Habana, December 5th-7th, 2017.The papers update the latest research in their field, carried out since the last conference in 2015.  Overall it gives a broad view of research on calcined clays and their application in the field of construction, which will stimulate further research into calcined clays for sustainable concrete.
Muthengia -- Promising Early age evaluations of Fly ash - Calcined marl - OPC ternary cement, by Serina Ng and Tone Østnor -- Applicability of lime reactivity strength potential test for the reactivity study of limestone calcined clay cement, by Anuj Parashar, Vineet Shah, Shashank Bishnoi -- Limestone and Calcined Clay Blended Cement Used as Low-Cost Binder to Reduce Heat Production and Potential for Delayed Ettringite Formation, by Jerry M. Paris and Christopher C. Ferraro -- Hydrate Phase Assemblages in Calcium Sulfoaluminate - Metakaolin - Limestone Blends, by M. Pedersen, B. Lothenbach, F. Winnefeld, and J. Skibsted -- Influence grinding procedure, limestone content and PSD of components on properties of clinker-calcined clay-limestone cements produced by intergrinding, by A. Pérez, A. Favier, K. Scrivener and F. Martirena -- Durability of concretes made with calcined clay composite cements, by Roland Pierkes, Simone E. Schulze, Jörg Rickert -- Alkali-activation of calcined clays - past, present and future, by John L. Provis -- Influence of a calcined clay and the temperature on the hydration of an oilwell cement, by Juan Alberto Ribalta, Adrián Alujas Díaz and José Fernando Martirena -- Influence of the kind of mineral addition and the seawater on the hydration of a Portland cement, by Juan Alberto Ribalta*, Leidys Laura Pérez and Adrián Alujas Díaz -- Standardization strategy of Low Carbon Cement in Cuba. Case study for "Siguaney" Cement Factory, by D. Rocha, R. Almenares, S. Sanchez, A. Alujas, F. Martirena -- Antibacterial metakaolin-based geopolymer cement, by Jose-Carlos Rubio-Avalos -- Identification of reactive sites in calcined kaolinite and montmorillonite from a combination of chemical methods and solid-state NMR Spectroscopy, by C. Ruiz-Santaquiteria and J. .
Keywords: Building materials; Inorganic chemistry; Economic development; Mineralogy; Building Materials; Structural Materials; Inorganic Chemistry; Development Studies; Mineralogy